2015
DOI: 10.1007/s00421-015-3304-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscle damage and repeated bout effect following blood flow restricted exercise

Abstract: We conclude that unaccustomed single-bout BFRE performed to failure induces significant muscle damage. Additionally, both ECC and BFRE can precondition against muscle damage induced by a subsequent bout of BFRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(138 citation statements)
references
References 42 publications
10
116
7
1
Order By: Relevance
“…Interestingly, the marked increases in plasma CK values reported previously were paralleled by fairly high DOMS scores (∼5 out of 10) (Sieljacks et al . ), which is higher than DOMS reported at rest and during muscle activity in the present study (median: 4.6–5.6 and 7.4–10.3 out of 100). Thus, overall there seem to be contrasting muscle damage responses between studies.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Interestingly, the marked increases in plasma CK values reported previously were paralleled by fairly high DOMS scores (∼5 out of 10) (Sieljacks et al . ), which is higher than DOMS reported at rest and during muscle activity in the present study (median: 4.6–5.6 and 7.4–10.3 out of 100). Thus, overall there seem to be contrasting muscle damage responses between studies.…”
Section: Discussioncontrasting
confidence: 78%
“…These observations are in stark contrast to the marked CK increases (∼36‐fold) recently reported 48 and 96 h after acute BFR exercise (Sieljacks et al . ). However, other studies have failed to detect CK changes after acute (≤24 h) or longitudinal BFR exercise (Takarada et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the finding of a clear increase in the number of myonuclei supports that type I fibre hypertrophy did indeed occur. In this regard, although a previous study from our laboratory demonstrated that unaccustomed BFRE performed to volitional failure could produce muscle-damaging responses, these responses were attenuated upon repeated exposure single-bout BFRE, indicating that muscle damage is negligible in the trained state (Sieljacks et al, 2016). Alternatively, increased myonuclear numbers may relate to regenerative processes in response to exerciseinduced muscle micro-damage (Paulsen et al, 2012).…”
Section: Impact Of Bodyweight Bfre On Muscle Protein Accretion and Stmentioning
confidence: 86%
“…Sieljacks et al . () investigated the effects of low‐intensity ECC with BFR. They observed no changes on muscle damage markers when BFR was applied.…”
Section: Discussionmentioning
confidence: 99%